NCOG-26. IMPACT OF GENDER ON TUMOR TREATING FIELDS COMPLIANCE IN PATIENTS WITH GLIOBLASTOMA - Karpf, Lauren (Neuro Oncol, 2020)
BACKGROUND: Tumor treating fields (TTFields) has emerged as a novel antimitotic modality to treat glioblastoma (GBM). Recently, a positive association was reported between TTFields dose at the tumor bed and survival outcomes in GBM patients. Dose density depends upon power density and compliance rate (cumulative amount of time TTFields therapy is delivered to the patient). Increased compliance with TTFields has been proposed as an independent prognostic factor for improved clinical benefits. There is evidence that females tend to respond better than males to standard therapy. However, the impact of gender and age on TTFields compliance is not fully understood in GBM patients. OBJECTIVE: To investigate potential interactions amongst age, gender and TTFields compliance in GBM patients. METHODS: A cohort of 16 patients (males =9; females=7; mean-age=60.8±7.6years) with newly diagnosed and recurrent GBM receiving TTFields were analyzed retrospectively. Device usage time was collected from internal log files in each case. The mean duration of TTFields therapy in patients was 4 months. Chi-square and independent sample T-tests were performed to evaluate differences in compliance rates based on patient age and gender and to examine gender-age relationships. Additionally, Pearson correlation analyses were performed to determine associations between gender and compliance rates. The probability (p) value of 0.05 was considered significant. RESULTS: A trend (p=0.067) towards greater TTFields compliance was observed in females (80.1±0.11%) versus males (63.0±0.22%). Additionally, there was a strong positive correlation (R=0.73; p=0.058) between age and compliance rates for female patients. There were 6 patients ≥ 65 years and 10 patients < 65 years. However, we did not find significant differences in compliance rate and gender variables between patients ≥ 65 years and < 65 years of age. CONCLUSIONS: Our results demonstrate gender influences TTFields compliance amongst GBM patients. However, future studies with larger cohorts are warranted to validate these findings.